Influence of designs of weaves on acoustic attenuation of fabrics. (July 2019) - Barburski, Marcin; Blaszczak, Jarosław R; Pawliczak, Zbigniew
The results of acoustics tests of different structure woven fabrics are presented. The researches were performed in the aeroacoustic anechoic chamber. Ten fabrics were tested (four of them with honeycomb 3D design) to check their acoustic properties. The tests were conducted inside lower and medium acoustical frequency zones. The presented studies showed that all fabrics with honeycomb weaves had much less attenuation than other fabrics, mostly due to less dense structures at higher thicknesses and more open internal structures. Having analyzed the obtained results, some comments are shown and possibilities of using such woven structures are proposed.